Faktor-Faktor yang Memengaruhi Pergerakan Indeks Harga Saham Gabungan di Bursa Efek Indonesia Periode 2018-2023 - Albert Pangestu Handoyo; Faizal Rizky Yuttama; Puspita Lianti Putri (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
The effect of exchange rate, BI Rate, and inflation on the movement of the Composite Stock Price Index on the Indonesia Stock Exchange for the period 2018- 2023. The study aims to determine the factors that affect the movement of the Joint Stock Price Index with independent variables exchange rate, BI Rate, and inflation, taking into account the phenomenon of Covid-19. This study uses quantitative methods using secondary data. The Data were analyzed using multiple linear regression methods, and divided into 2 periods before Covid-19 and after Covid- 19. The results showed that before Covid-19 the exchange rate had a significant negative effect on the movement of the Composite Stock Price Index, the BI Rate had a significant positive effect on the movement of the Composite Stock Price Index, and inflation had a positive insignificant effect on the movement of the Composite Stock Price Index. After Covid-19, the exchange rate did not have a positive effect on the movement of the Composite Stock Price Index, the BI Rate did not have a negative effect on the movement of the Composite Stock Price Index, and inflation had a significant positive effect on the movement of the Composite Stock Price Index.